Analyzing the Eleventh-Year-Students’ Descriptive Writing Skills Documented in the Academic Year of 2017-2018 - Prastika, Winda; Setiawati, Endang Eko; Sumekto, Didik Rinan (LPPM Universitas Pancasakti Tegal, 2018)
This research aims at analyzing students’ descriptive writing skills that engage the academic performance among the eleventh-year-students in the academic year of 2017-2018. This research applied for the quantitative method and involved 60 students of the eleventh year students of Islamic state high school (Madrasah Aliyah Negeri 1) Klaten as the respondents. Data collection used the students’ descriptive writing test. Data were statistically analyzed the SPPS program to gain the descriptive analyses. The finding showed that the overall achievement of students’ organization component was in the average level with 73.3% respondents, mechanics component was in the average level with 66.7% respondents, evidence component was in the average category with 46.7% respondents, and sentence structure component was in the average level with 55% respondents. The lowest score gained in descriptive writing was sentence structure (M = 2.533; SD = .700) and and the highest score was on organization component (M = 2.733; SD = .446). This research concludes that students’ descriptive wrting skills laid on the average category.